A colaboração no processo avaliativo: seus efeitos na elaboração de provas, no ensino e na formação futuros professores de inglês - Porto, Cristina Vasconcelos (2016)
This study aims at describing and understanding the experiences of developing language assessment of five pre-service English teachers from Universidade Federal do Pará. This research also aims at documenting the experiences these teachers had during the process of constructing their tests alone and in collaboration with their English pre-service teachers peers. To conduct this investigation, the tests were analysed in the light of the qualities of language test (content validity and reliability) and the principles of the communicative approach. This study also investigates the perceptions of the teachers on their experiences of collaboration during the process of constructing their tests. Adopting a qualitative perspective in the data collection and analysis, this case study was conducted in 2014, and the theoretical framework was based on studies about experiences, sociocultural theory and language assessment. Data were obtained through questionnaire, interview, verbal protocol, field notes, audio and video recording of the interactions the participants engaged in, and the tests ellaborated by them. Amongst the conclusions we arrived at, we observed that, through collaboration, the participants not only constructed better tests, but they also had opportunities to give their opinions, to share experiences and to reflect on their teaching practice, understanding the important role of evaluation in improving teaching and learning processes. This study has implications to initial teacher education, indicating that pre-service teachers need to have a more active role in language assessment and need to become aware that working collaborativelly can create professional development opportunities for themselves.